Assessing speaking in context expanding the construct and its applications - Salaberry, M. Rafael 1963-; Burch, Alfred Rue 1974- (Second language acquisition, 2021)
This book takes a critical perspective of research on assessing speaking in second and foreign languages. Chapters focus on the complexity brought about by actual interactional competence in speaking tasks and discuss how testing and assessment models and practices can incorporate recent research on the dynamic and situated nature of language use